2020
DOI: 10.1177/0956462420921715
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing among pregnant women with prenatal care in the United States: An analysis of the 2011–2017 National Survey of Family Growth

Abstract: Although there has been significant progress in reducing perinatal human immunodeficiency virus (HIV) transmission, the United States is yet to meet the proposed elimination goal of less than one infection per 100,000 live births. Failure to screen all pregnant women for HIV as recommended by the Centers for Disease Control and Prevention can result in missed opportunities for preventing vertical transmission of HIV with antiretroviral drugs. Using the 2011–2017 National Survey of Family Growth, this study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This finding revealed that poverty is significant influencing factor associated with HIV testing during ANC. Our findings, which showed that there is significant inequality in HIV testing during ANC between richer and poorer quintile of women, are consistent with findings from low -middle-income countries [ 20 , 50 , 51 ]. We found that education, place of residence, regular exposure of mass media, and comprehensive knowledge of HIV/AIDS made a considerable contribution to observed socio-economic inequalities in HIV testing during antenatal period.…”
Section: Discussionsupporting
confidence: 91%
“…This finding revealed that poverty is significant influencing factor associated with HIV testing during ANC. Our findings, which showed that there is significant inequality in HIV testing during ANC between richer and poorer quintile of women, are consistent with findings from low -middle-income countries [ 20 , 50 , 51 ]. We found that education, place of residence, regular exposure of mass media, and comprehensive knowledge of HIV/AIDS made a considerable contribution to observed socio-economic inequalities in HIV testing during antenatal period.…”
Section: Discussionsupporting
confidence: 91%
“…More details about the PRAMS surveillance system have been described elsewhere https://www.cdc.gov/prams/index.htm. 16 This report is a secondary data analysis of data collected by seven states (Alabama, Alaska, Arkansas, Maryland, Massachusetts, Mississippi, and Nebraska) that asked an optional question about the receipt of HIV testing during pregnancy and achieved a targeted weighted annual response rate of at least ⩾ 55% (2016 and 2017) or ⩾ 50% (2018 and 2019) on their PRAMS survey in one or more of the study years. State data were included for each year the state achieved the required weighted annual response rate.…”
Section: Methodsmentioning
confidence: 99%
“…More details about the PRAMS surveillance system have been described elsewhere https://www.cdc.gov/prams/index.htm . 16 …”
Section: Methodsmentioning
confidence: 99%
“…We have addressed one area, for women who already access antenatal screening, whereas a comprehensive program should ensure all women can access screening during pregnancy or at delivery. 11,12 During the consultation it was apparent that practices surrounding HIV screening in pregnancy are not transparent to the community sector and policy makers and they may not reflect current bestpractice; therefore, we strongly recommend national oversight of this area, starting with an audit of current antenatal HIV testing policy and uptake in all localities (including ethnicity data), and an unequivocal move to national opt-out testing.…”
Section: Opt-in Opt-outmentioning
confidence: 99%